Ethnomathematics of Buying and Selling Transactions Conducted by Traders in Beriman Tomohon Market - Rine Ervine Margaretha Supit; Vivian E. Regar; Marvel G. Maukar (Departement of Mathematics Education, 2023)
The goal of this study is to detail the purchasing and selling procedures employed by traders at the Tomohon faith market as well as the arithmetic computation techniques they employ. Research of this kind is qualitative. Interviewing and participant observation techniques were utilized to acquire the data. In this study, the data analysis is qualitative descriptive. Ten traders from the Tomohon faith market were chosen at random to participate as research subjects in this study. The study's findings demonstrate that Tomohon faith market vendors round up their prices when selling their items. The way that traders provide change is to round up the cash that needs to be paid in advance to the nearest tenth, then add it up until the whole sum matches the cash the buyer has paid. The methods used by research participants to calculate addition, subtraction, and multiplication differ significantly from those used in classroom instruction. The value 0, which functions as thousands, is always disregarded. Start by adding the thousands with the thousands, then the hundreds with the hundreds, to determine the total. Some people also finish first to the nearest tens value. If the number being decreased, for example, is 50,000 - 13,000, the reduction procedure is 13 to go to 20 less 7. Then 50 – 20 = 30. The result is 37, which equals 37,000. In addition, you must deduct the first tens of thousands from the second tens of thousands before removing the remaining part of the second figure. Multiply the number from the front number first, for instance, tens of thousands, then thousands, and so on, to calculate the multiplication technique. Find the number that can be divided by the divisor to calculate the division. The outcome of the previous division is then applied to the divided number. This process is continued until all the divided number has been used. The outcomes of these divisions should then be added.